A Stylistic Analysis of Rape Metaphors in Alice Sebold’s The Lovely Bones - Shahid, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2025)
Alice Sebold’s The Lovely Bones (TLB) portrays a young rape victim of fourteen, Susie Salmon, who was brutally beaten, raped, and murdered in a hole in the ground by an elderly man of thirty-six, Mr. Harvey. The representation of rape in Sebold’s TLB has been examined through a variety of perspectives by employing linguistic approaches to the meanings of rape metaphors. The studies on rape metaphors in TLB have indicated the details of rape events and rape victims’ experiences. Nevertheless, since rape metaphors are a part of rape victims’ cognition and thought systems, the findings of the existing studies on rape metaphors in TLB remain inadequate to understand the comprehensive meanings of rape metaphors (i.e., combining both linguistic and conceptual knowledge approaches) in literary language. It is due to the contemporary theory of metaphor, Conceptual Metaphor Theory (CMT) (Kovecses, 2002, 2010; Lakoff & Johnson, 1980, 2003), in which metaphors are not only language-based, intended to achieve rhetorical effects on the audience, but also an essential constituent of human thought and cognition. Accordingly, metaphors significantly influence our understanding of a concept in terms of another. In the existing literature on rape representation, very few studies have been conducted on conceptual metaphors of rape. Besides, the findings of the studies remain inconclusive as they are based on the phenomenon of cognition, ignoring the role of language and linguistic knowledge in constructing rape metaphors. Importantly, the theory of Lexical Concepts and Cognitive Models (LCCM) (Evans, 2006, 2009, 2010, 2013) claims that the integration of linguistic knowledge and conceptual knowledge is essential to have a comprehensive meaning and understanding of a metaphor. Therefore, in the current study, rape metaphors in Sebold’s TLB are investigated by incorporating both linguistic knowledge and conceptual knowledge. For this, theoretical approaches of literary stylistics (Leech & Short, 2007), CMT, and LCCM Theory have been applied to dissect rape metaphors in Sebold’s TLB. Three research questions were derived to guide the study: (1) What are the types of conceptual metaphors used to describe rape in Alice Sebold’s TLB? (2) How are the conceptual metaphors of rape constructed in Alice Sebold’s TLB? (3) What are the differences between the metaphorical constructions of rape in Alice Sebold’s TLB and the existing rape discourses? The findings of the study reveal a variety of categories of conceptual metaphors like animal metaphors, plants metaphors, objects and things metaphors, metaphors of human state and human experiences, metaphors of human activities, and personifications constructing the conceptual metaphors, such as RAPE VICTIMS ARE ANIMALS, RAPE VICTIMS ARE PREY, RAPE IS SILENCING, RAPE IS HUNTING, RAPE IS PSYCHOLOGICAL SUFFERING, RAPE IS HUMILIATION, and RAPE IS MUTILATION. Furthermore, the findings show that the metaphorical constructions of rape in TLB indicate how rape is constructed through the source domains related to the human experiences of animals, birds, plants, hunting, silencing, humiliating, killing, and torturing, exhibiting the reality of rape, the embedded horrors, and underpinning the gravity of pain and suffering of rape victims. Additionally, the findings show the significant differences in rape events and rape victims’ conceptualizations in Sebold’s TLB and other existing rape discourses, such as media discourses of rape, legal and rape trial discourses, political and war rape discourses, and religious discourses of rape. Moreover, the study provides the comprehensive meanings of rape metaphors in contrast to the perspective in which metaphors have traditionally been seen as merely linguistic and rhetorical devices. Overall, this study is a significant contribution to understanding rape and rape victims’ life experiences in TLB. Also, it will help us interpret the existing literature on rape, exposing the horrific reality of rape events and the traumatic experiences of rape victims that are metaphorically constructed and represented through literary language.